Pengembangan Medıa Swıvel Wheel Untuk Menıngkatkan Hasıl Belajar Sıswa Pada Mata Pelajaran IPS Dı Kelas VI Sekolah Dasar - Putri Pramestia Ningrum; Dahlan , Zaini (Jurnal Elementaria Edukasia, 2023)
The background of this research is the low student learning outcomes in social studies learning in class VI of elementary school. This study aims to develop Swivel Wheel media in improving student learning outcomes in social studies subjects in class VI SDN No 050668 L. Dalam. The method used in this study is the ADDIE Research and Development model which consists of 5 stages, namely the Analysis, Design, Development, Implementation, and Evaluation stages. The research data was collected using test and non-test instruments. The test instruments were in the form of descriptive questions to measure higher-order thinking skills and student learning outcomes, while the non-test instruments used in this study were (1) questionnaires; (2) interview guidelines; (3) field notes; (4) documentation; (5) literacy assessment. After the data is collected, the data is processed using a qualitative approach using inductive techniques and a quantitative approach using statistical tests. The results of the study show that Learning Media makes the classroom atmosphere come alive, students are enthusiastic about asking and answering questions, and students are also more enthusiastic about participating in learning so it has a very significant effect on student learning outcomes